Comparative Analysis of NOx Emission Reduction in Engines Using NiCo2O4 Nanoparticles without External Reductant at Low Temperatures: An Experimental Investigation. (16th September 2022) - Aswin, C. G.; Kumareswaran, A.; Lakshmanan, R.; Mathavan, S.; Andal, V.; Lakshmipathy, R.; Rico, Ivan Leandro Rodriguez
Abstract : Due to increasingly stringent rules, eliminating pollutants (NOx) emitted by diesel engines in the automobile sector remains an intriguing scientific and technological problem. To meet the strict NOx emission restrictions, a catalytic system with a high level of complexity, unit size, and quantity, as well as higher fuel consumption, is required. As a result, for a reduction in individual exhaust gas emissions, an after-treatment system for a diesel vehicle must employ integrated catalyst technology. For selective catalytic reduction of NOx without any external reductant, a highly effective catalyst "spinel nickel cobaltite" (NiCo2 O4 ) was produced using a polymeric precursor technique. In this work, an exhaust gas treatment system without external reductants using nano-NiCo2 O4 as catalyst was designed and fabricated, for NOx control in diesel and petrol engines at low temperature. In order to determine the NOx conversion efficiency in the selective catalytic reduction system, tests were carried out at different engine loads. The system was supposed to be cost-effective due to the nano-NiCo2 O4 catalyst's ability to work at low temperatures. The findings proved the developed SCR system's potential to reduce NOx emissions. At a high load, the nitric oxide (NO) emissions were reduced by 54 and 96 percent, respectively, without increasing HC, CO, and CO2 emissions or compromising efficiency.